Watu Ireng Sukses: Future Challenges Of Coal Business In Jambi Province - Firmansyah, Choiril (International Journal of Social Service and Research, 2024)
PT Watu Ireng Sukses is a mining concession located in Jambi Province. It began operating in mid-2021 despite obtaining permits from 2019 that will end in 2032. The decision to start operations in 2021 was due to good prices that made it possible to start operations that year. In 2021-2023 the price of Coal was at its peak, and in 2022, precisely in March, with ICI-1 reaching $308.31. The steps include identifying major coal companies through thorough research, collecting data related to production, market share, mine location, infrastructure and other factors, then continuing with an analysis of the challenges they face, such as regulatory changes, decreased market demand and environmental problems. Responding to significant price changes, the Indonesian government took advantage of the situation in increasing government revenue from the Coal sector. Exactly 5 months after a very significant price increase, the government conducted an evaluation to increase the country's profits from this potential. PT WIS has sufficient coal reserve potential to expand additional production capacity, but all of it must go through processes such as project feasibility evaluation and environmental impact feasibility evaluation.